(untitled) (Journal of the Bangladesh Agricultural University, 2017)
An experiment was conducted in the Field Laboratory, Department of Entomology, (BAU), Mymensingh on the varietal preference of okra jassid, Amrasca devastans (Dist.) using 14 okra varieties viz. F1 Tamanna, Hybrid Okra Gunyon, Okra F1 Green Soft, OK 285, Okra F1 Green Star 33, F1 Hybrid Fresh Power, F1 Hybrid Sarosh 3, Hybrid Okra (MDR), Okra Nabil, BARI-1 (Samrat), Hybrid Chamak and Local variety during March to June 2014. The results indicated that host preference of jassid differed significantly among the 14 varieties tested. Three varieties viz. Hybrid Chamak, Arka Anamika and Kolatia were the least preferred by jassid. Five varieties viz. Okra Nabil, Hybrid Okra (MDR), F1 Hybrid Fresh Power, Local variety, and OK 285 were comparatively highly preferred and rest of the six varieties viz. Okra F1 Green Star 33, BARI-1 (Samrat), F1 Tamanna, F1 Hybrid Sarosh 3, Hybrid Okra Gunyon, and Okra F1 Green Soft were moderately preferred by jassid. This variation of preference of okra jassid might be due to different morphological and physiological characters of selected varieties. It could be concluded that comparatively resistant varieties selected from the present study might be incorporated to develop of IPM package for jassid. J. Bangladesh Agril. Univ. 15(2): 227-233, December 2017